Immune regulation mechanism of vitamin D level and IL-17/IL-17R pathway in Crohn's disease - Xia, Yanli (Exp Ther Med, 2019)
Immune regulation mechanism of vitamin D level and interleukin (IL)-17/IL-17 receptor (IL-17R) pathway in Crohn's disease was studied. Of 40 clean mature healthy rats, 10 rats were used as control group based on random number table, the remaining 30 rats to establish Crohn's disease rat models. After successful modeling, 30 rats were divided into model group, low-dose group and high-dose group with random number table. On the 1st day after modeling, rats in low-dose group were given a single dose of 1,750 IU of vitamin D, and rats in high-dose group a single dose of 7,500 IU of vitamin D. Changes in the condition of rats after modeling were observed and scored. Enzyme-linked immunosorbent assay was used for detecting IL-12, IL-17 and CXCL11 levels, western blotting for detecting IL-17R level, and flow cytometry for detecting Th1 cell and Th17 cell levels in the lamina propria of colon mucosa. Disease activity index scores were significantly lower in low-dose group and high-dose group of rats than those in model group (P<0.05). Those were significantly lower in high-dose group of rats than those in low-dose group (P<0.05). IL-17 and IL-17R levels were significantly lower in high-dose group of rats than those in low-dose group (P<0.05). Th1 cell level was significantly higher in high-dose group of rats than that in low-dose group (P<0.05), but Th17 cell level was lower than that in low-dose group (P<0.05). IL-12 levels were significantly higher in model group, low-dose group and highdose group of rats than those in control group (P<0.05). CXCL11 levels were significantly lower in model group, low-dose group and high-dose group of rats than those in control group (P<0.05). Vitamin D can effectively treat Crohn's disease, which may improve the chemotaxis and differentiation of Th1 cells by inhibiting IL-17/IL-17R pathway, thereby improving immune function and reducing the severity of disease.